PRELIMINARY PHYTOCHEMICAL STUDY OF THE ECUADORIAN PLANT CROTON ELEGANS KUNTH (EUPHORBIACEAE) - Herrera, Claudia; Pérez, Yanely; Morocho, Vladimir; Armijos, Chabaco; Malagón, Omar; Brito, Beatriz; Tacán, Marcelo; Cartuche, Luis; Gilardoni, Gianluca (Journal of the Chilean Chemical Society, 2018)
The species Croton elegans Kunth, belonging to the family Euphorbiaceae and known with the common name “mosquera”, is a native medicinal plant of Ecuador. Due to its medical applications, we are interested in secondary metabolite composition. After extraction with hexane and preparation of the alkaloid extract, preparative chromatographic fractionation in both normal and direct phase was performed. 1H NMR, 13C NMR, HSQC and HMBC experiments, together with polarimetric measurements, were conducted in order to characterize the purified compunds. Two triterpene metabolites (friedelin and cycloeucalenol) and two morphinan alkaloids ((+)-pallidine and (+)-O-methylpallidine) were obtained in a pure form. This work represents the first report on the phytochemistry of C. elegans and probably the second publication on the natural (+)-pallidine alkaloid.